RESEARCH ETHICS MANAGEMENT IN EDUCATIONAL STUDIES: NAVIGATING SOCIAL RESPONSIBILITY AND CULTURAL SENSITIVITIES - Tuerah, Paulus Robert; Sumilat, Meiny Conny; Tumilantouw, Nicky Marselina; Katiandagho, Deasy V.; Katuuk, Ariel Ferdinand; Kapoh, Defnny Christin; Sumual, Tinneke Evie Meggy (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
This study examines the ethical management of educational research, focusing on social responsibility and cultural sensitivity. It aims to address challenges in balancing academic goals with ethical principles, particularly in diverse cultural contexts. The study employs a qualitative literature review method, analyzing theoretical and empirical sources to explore the intersection of research ethics and cultural awareness. The findings highlight three main issues: low awareness of research ethics, neglect of cultural sensitivity, and minimal integration of social responsibility. Researchers in remote areas often lack knowledge of ethical guidelines, leading to practices that compromise participants' rights. Cultural insensitivity is prevalent due to a universalistic approach that overlooks local values, creating tensions between researchers and communities. Additionally, research outcomes often fail to address community needs, as they are more focused on academic achievements than tangible societal benefits. This study recommends integrated ethics training, participatory research approaches that respect local values, and the adoption of transformative paradigms emphasizing community empowerment. These strategies aim to enhance the relevance, ethical integrity, and social impact of educational research. By addressing these challenges, researchers can contribute to more inclusive and socially responsible practices, bridging the gap between theory and practice in diverse educational settings.